Modifikasi Mesin Peniris Minyak Sistem Spinner - Harmen harmen; Imam Sofi'i; Ridwan Baharta (Jurusan Teknologi Pertanian, 2020)
The process of draining oil is one of the processes that can affect the oil content of the frying or chips. The oil that is left in a lot of fried food or chips when stored for a long time will cause a rancid smell. Meanwhile, if consumed directly, it will affect the health of consumers because of high cholesterol levels. Most people do not know the consequences that occur if they consume excess oil. People who already know cannot do anything because the oil draining machines on the market are still quite expensive and their working capacity is limited. In the previous research, a draining machine with a tube system with a diameter of 40 cm and a height of 22.2 cm was made with an rpm of 517. Within 5 minutes this system reduce oil content from 27% to 24,65% . The data shown in strightline gaphic trend that mean the reduction oil conten is not optimal yet . For this reason, this research will be redesigned by extending the spinner axis and adding the bearings to 2 units, it is hoped that this addition will stabilize the spinner rotation, the rotation can be increased and the ability to reduce oil content increases. extending the drain axis and increasing the position of the bearing to 2, the draining machine has been able to function properly until 967 rpm rotation, from the test results for draining the cassava chip oil, within 5 minutes, the slicer with a rotation of 598 rpm can reduce 2.29%, 727 rpm 2.93%, and 967 rpm 4.27% rotation.